Analysis of Andragogy Approach in Aspects of Tutor Performance According to Citizens Learning Equality Education - Vevi Sunarti; Jamaris; Solfema; Mega Iswari; Abna Hidayati; Reza Gusmanti (Bisma The Journal of Counseling, 2022)
The need for the application of andragogy principles in the adult learning approach is because learning efforts are different from children's learning efforts. Children's learning transmits a number of experiences, knowledge and skills in order to prepare children to face life in the future. In contrast, adult learning emphasizes more on guiding and helping adults to find knowledge, skills and attitudes in order to solve the problems of life they face. The accuracy of the approach used in organizing a learning activity will affect the success of the learning objectives. This study aims to 1) analyze the tutor's andragogy approach according to the learning community in the aspect of communication, 2) analyze the tutor's andragogy approach according to the learning community in terms of physical appearance. The method of collecting data is by distributing questionnaires to 40 residents learning equality education. The analytical method used is descriptive analysis of the quality of the results of the collection of questionnaires, it can be concluded that; 1) the andragogy approach to the performance aspect of tutors in terms of how to communicate tutors according to learning residents is still low/not yet communicative; 2) the andragogy approach in the aspect of tutor performance in terms of physical appearance according to learning residents is still low/less attractive.